SUSTAINABLE HUMAN RESOURCE MANAGEMENT PRACTICES IN MICRO, SMALL AND MEDIUM ENTERPRISES - Farida Farida (SEAN Institute, 2023)
Sustainable human resource management is defined as a strategic approach in managing human resources that not only pays attention to economic aspects, but also social and environmental aspects. This research aims to explore and analyze the implementation of sustainable human resource management in Micro, Small and Medium Enterprises (MSMEs). This research uses a qualitative approach with descriptive methods. The research results show that the implementation of sustainable human resource management (HRM) practices in Micro, Small and Medium Enterprises (MSMEs) has a significant positive impact. MSMEs that have a high awareness of sustainability take concrete action in implementing HRM that focuses on environmental, social and employee welfare aspects. Completeness in HRM practices, such as recruitment based on sustainability values, sustainability-related training, and career planning that considers contributions to sustainability goals, makes a positive contribution in creating competitive advantage. With a good reputation in sustainability, the ability to attract and retain high-quality employees, and environmentally friendly product innovation, MSMEs have succeeded in achieving holistic business sustainability while providing a positive impact on the environment and society.